ANALISIS DEBIT DAN TINGGI MUKA AIR BANJIR SUNGAI WAY RUHU KOTA AMBON - Laipeny, Teddy Jackson; Warniyati, Warniyati; Sihombing , Tri Octaviani; Tutkey, Monica R. (JURNAL SIMETRIK, 2025)
The Way Ruhu River is one of the rivers in Ambon City, Maluku, empties into Ambon Bay, has a length of 8.37 km, and is one of the rivers that is prone to flooding. There have been several floods on this river and the most severe occurred in early August 2012 where flash floods occurred and caused considerable losses to the people living around the Way Ruhu River. The research location was carried out on the Wai Ruhu River in Ambon City - Maluku Province. Geographically, the Wai Ruhu River is located between 3°39'44.18" - 3°41'39" South Latitude and 128°11'49.06" - 128°13'46.47" East Longitude. The stages of this research are processing rainfall data, choosing the appropriate rainfall frequency distribution method. The distribution of rainfall frequency referred to in this case is the normal method, Gumbel, Normal Log and Pearson III Log. Testing the accuracy of the results of this method using the Chi Square method. Calculating the planned discharge using the HSS Nakayasu Method. Conclusions from the results of the analysis of the cross-sectional capacity of the Way Ruhu River using HEC-RAS, the highest water level considered is at point S14. At the 10 year discharge period, the flood height was 0.16 m with a discharge of 237.04 m3/sec, 25 years was 0.64 m with a discharge of 282.43 m3/sec, 50 years was 0.89 m with a discharge of 316. 69, 100 years with a discharge of 351.16 m3/s, and for 200 years of 1 m with a discharge of 385.10 m3/s. The solution to the capacity of the Way Ruhu River is to improve the river cross-section. It is necessary to carry out routine maintenance on the canal such as cleaning grass and rubbish because this can affect the storage capacity. There is a need to provide outreach to the community about the impacts caused by the overflow of the Way Ruhu River so that the community and the Regional Government can work together in maintaining and maintaining the infrastructure that has been built. Keywords: River, Discharge, Flood, HEC-RAS